Clarissa Harlowe; or the history of a young lady $1 (BVolume 7s - Richardson, Samuel, 1689-1761 (Salt Lake City, UT : Project Gutenberg, 2004)
"Clarissa Harlowe; or the History of a Young Lady $1 (BVolume 7" by Samuel Richardson is a novel written in the early 18th century. This volume continues the epistolary tale of Clarissa Harlowe, detailing her profound struggles, virtue, and relationships with various characters, primarily Mr. Lovelace and her close friend Miss Howe. The narrative unfolds through letters that convey the emotional turmoil and moral dilemmas faced by the young lady, positioned in a conflict between societal expectations and individual desires. The opening of this volume presents a series of letters exchanged among key characters, highlighting Clarissa's ongoing battle with despair and the manipulations of Lovelace. Miss Howe expresses her concern for Clarissa$1 (Bs mental state while urging her to find solace in her virtue despite the harshness of their society. Lovelace, meanwhile, remains fixated on Clarissa, oscillating between jest and sincere regret over losing her, demonstrating his complex nature. As their correspondences unfold, the tone oscillates between hope and indignation, revealing the intricate web of relationships and tensions that characterize Clarissa's struggle for autonomy and dignity in a world rife with challenges. (This is an automatically generated summary.)s
Release date is 2004-04-01
Produced by Julie C. Sparks and David Widger
Keywords: England -- Fiction; Psychological fiction; Epistolary fiction; Conflict of generations -- Fiction; Kidnapping victims -- Fiction; Young women -- Crimes against -- Fiction; Rape victims -- Fiction